2008
DOI: 10.4049/jimmunol.180.5.3426
|View full text |Cite
|
Sign up to set email alerts
|

Human Factor H Interacts Selectively with Neisseria gonorrhoeae and Results in Species-Specific Complement Evasion

Abstract: Complement forms a key arm of innate immune defenses against gonococcal infection. Sialylation of gonococcal lipo-oligosaccharide, or expression of porin 1A (Por1A) protein, enables Neisseria gonorrhoeae to bind the alternative pathway complement inhibitor, factor H (fH), and evade killing by human complement. Using recombinant fH fragment-murine Fc fusion proteins, we localized two N. gonorrhoeae Por1A-binding regions in fH: one in complement control protein domain 6, the other in complement control proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
143
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(147 citation statements)
references
References 74 publications
4
143
0
Order By: Relevance
“…In Neisseria meningitidis, sialylation of LOS results in a reduced phagocytosis by DCs, without influencing cytokine secretion (29). Sialylation of LOS may also inhibit complement activation, as was demonstrated for Neisseria gonorrheae (30). Sialylation of LOS helps C. jejuni to invade intestinal epithelial cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…In Neisseria meningitidis, sialylation of LOS results in a reduced phagocytosis by DCs, without influencing cytokine secretion (29). Sialylation of LOS may also inhibit complement activation, as was demonstrated for Neisseria gonorrheae (30). Sialylation of LOS helps C. jejuni to invade intestinal epithelial cells (16).…”
Section: Discussionmentioning
confidence: 99%
“…They may interact with host regulators, such as binding Factor H, which increases the degradation of C3b and reduces formation of C3 convertase, thereby limiting complement activity [151]. This phenomenon is well characterized in the Nesseria family of pathogens, including N. meningitidis and N. gonorrhoeae, both of which have been shown to bind to Factor H in an attempt to avoid destruction by the host complement system [42,152]. Interestingly, recent structural determinations of the N. meningitidis: Factor H complex have revealed that the pathogen subverts the host complement system through the use of protein mimetics of host carbohydrate motifs, thereby recruiting Factor H to its surface and evading destruction [153].…”
Section: Complement Evasion/subversion Strategies Of Microorganismsmentioning
confidence: 99%
“…During extracellular growth in the human body, N. meningitidis is exposed to complement. A mechanism that confers complement resistance is the recruitment of a molecule that down-regulates complement activation, complement factor H (fH), to the bacterial surface by factor H-binding protein (fHbp) (Schneider et al 2006;Ngampasutadol et al 2008). N. meningitidis fHbp binds fH from humans, but not fH from primates or mice (Granoff et al 2009).…”
Section: Iron Acquisition and Complement Resistancementioning
confidence: 99%